Oral immunization of mice with Lactococcus lactis expressing Shiga toxin truncate confers enhanced protection against Shiga toxins of Escherichia coli O157:H7 and Shigella dysenteriae. Issue 10 (28th August 2019) - Sreerohini, Sagi; Balakrishna, Konduru; Parida, Manmohan
Abstract : Regardless of the communal impact of Shiga toxins, till today neither a specific treatment nor licensed vaccine is available. Lactococcus lactis ( L. lactis ), generally regarded as safe organism, is well known to provide a valuable approach regarding the oral delivery of vaccines. This study was undertaken to evaluate the protective efficacy of Stx2a1 expressed in nisin‐inducible L. lactis, against Shiga toxins (Stx1, Stx2) in mouse model. Oral immunization of BALB/c mice with LL ‐ Stx2a1 elicited significant serum antibody titer with elevated fecal and serum IgA, along with minimized intestinal and kidney damage resulting in survival of immunized animals at 84% and 100% when challenged with 10 × LD50 of Escherichia coli O157 and Shigella dysenteriae toxins, respectively. HeLa cells incubated with immune sera and toxin mixture revealed high neutralizing capacity with 90% cell survivability against both the toxins. Mice immunized passively with both toxins and antibody mixture survived the observation period of 15 days, and the controls administered with sham sera and toxins were succumbed to death within 3 days. Our results revealed protective efficacy and toxin neutralization ability of LL‐Stx2a1, proposing it as an oral vaccine candidate against Shiga toxicity mediated by E. coli O157 and S. dysenteriae .